Electric therapy is used to reduce pain in a mother giving birth - Hidayah, Nur; Prasodjo, Ipin; Lestari, Puji Sri (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background:Pain during labor is a physiological response but can result in an increase in catecholamines which result in disrupting uterine contractions which can cause uterine inertia, prolonged labor, inadequate oxygenation to the fetus and fetal distress, as well as death of the mother and/or fetus if labor pain is not treated. According to (Utami & Putri, 2020) Severe pain can affect the increase in heart rate, respiratory system, increase in blood pressure and can cause stress, thereby inhibiting the release of the hormone oxytocin which results in inadequate contractions and disruption of cervical dilatation. Uterine contractions cause complaints of labor pain which can cause anxiety and fatigue in the mother during labor and have a negative influence on the progress of labor and the well-being of the fetus.Non-pharmacological pain management includes administering electrical therapy (TENS). Transcutaneous electrical nerve stimulation (TENS) is a therapy that uses electric current to treat pain due to various conditions, ranging from nerve disorders, disorders, to pain due to childbirth. Objectives of this research is to find out how much influence electrical therapy has in reducing pain in mothers giving birth. Methods The quasi-experimental research design uses a one group pretest-posttest design. The research population was mothers in the first stage of labor in the Sukoharjo Independent Midwife Practice area. The sampling technique was total sampling with a sample size of 20 people. Results obtained a reduction value of 1.55 (mean diff.) or a reduction of 23.2% and p=<0.001 (p<0.05) which means there is a significant difference in the pain scale before and after electrical therapy. therapeutic treatment. Conlusions, electrical therapy is effective in reducing pain in mothers giving birth.Key words: electrical therapy, labor pain, mother giving birth.